OPTIMALISASI PERANCANGAN VIDEO PEMBELAJARAN BAHASA INGGRIS BERBASIS WEB - Susanto, Herri; Pramudiningtyas, Rizki; Mukhrianto, Muri (Universitas Pendidikan Indonesia, 2014)
The purpose of the study generally is to facilitate high school students preparation for National Test and State/private Entrance Test and specifically the purposes are 1)to increase the activity of English learning videos through website, 2) to increase the learning activity through internet. The stages of this research consists of 5 stages such as; a) capturing English learning videos, b) creating website, c) uploading the videos to the website, d) launching the website to the third year of Bontang State Vocational School 3, and e) evaluating the website content. The results show that video learning designs is the most chosen feature(89%) than other features on the website. Furthermore, the questionaires reaveal that 100% give positive responses to the website given.